Antioxidant, physicochemical and mineral evaluations of Spondias mombin crude fruit juice - Coolborn, Akharaiyi Fred; Esther, Boboye Bolatito; Akinsola, Akinyosoye Felix; Afolabi, Oso Benjamin (Acta Biologica Szegediensis, 2016)
Edible fruits have potential health benefits regarding their richness in minerals, nutrients, vitamins and antioxidant. In view of the medicinal potential of the leaves and stem bark extracts of Spondias mombin, this study aimed to determine the antioxidant, physicochemical and mineral contents of the crude fruit juice of S. mombin for its employment in health promotion and traditional use for medicine. Free radical scavenging power of 93.97 ± 64.8 μmol (TE) and Ferric reducing power (FRAP) of 11.8 ± 0.2 μmol (AAE) were observed in vitro from the crude fruit juice. The physicochemical property of the crude fruit juice yielded proximate compositions of protein (6.03 ± 0.44), fat (1.85 ± 0.03), pH (3.63 ± 0.11), fibre (0.64 ± 0.02), moisture (80.60 ± 0.22%), ash (0.54 ± 0.03), carbohydrate (11.61 ± 0.34) and titratable acidity (28.52 ± 0.14). Trace elements from the crude fruit juice are in the amounts of 276.27 ± 2.65 for potassium, 1.15±0.01 (manganese), 0.121 ± 0.32 (copper), 4.45 ± 1.42 (sodium), 136.42 ± 1.35 (zinc), 12.36 ± 0.03 (magnesium), 0.01 ± 0.00 (lead), 28.22 ± 1.02 (phosphorus), 13.04 ± 0.53 (calcium) and 0.48 ± 0.01 (iron).